Economics banking efficiency in selected African countries in the post-reform period - Mzee, Said Seif (2013)
Banks play an important role in the developing economies as they intermediate between the savings and the demand for investment and consumption funds that finance the development of business and trade. To efficiently and effectively perform this function and help optimize the allocation of scarce investment funds, evaluation of banking sector efficiency is necessary. Not much has been documented on the efficiency of banks in Africa due to a combination of several reasons such as in availability of reliable data,corporate non-transparency, and political and economic uncertainty. Therefore, to date there is no comprehensive evidence documented on banking efficiency in Africa. However in recent years, most of the African countries had some form of economic and financial reforms initiated that has attracted foreign investment in their economies and had some observed improvements in their banking system to support this new development. This study fills this gap by analyzing cost and profit efficiency and tests the management behavior of 128 commercial banks in six African countries during 1998 to 2011 using DEA technique. The determinants of the banking efficiency were also investigated using the Generalized Least Square (GLS), management behaviour were examined using Generalized Method of Moment (GMM), and the causal relationship between bank efficiency and economic growth using Granger causality approach. The findings are inconclusive for commercial banks in Africa. Mixed results were observed for banks in Algeria and South Africa, and Tanzania are found to be more profit efficient,whereas banks in Egypt, Kenya, and Nigeria found to be more cost efficient. The implication of these findings is that commercial banks in Algeria, South Africa, and Tanzania are more efficient in generating profit than controlling cost, while banks in Egypt, Kenya, and Nigeria are more efficient in controlling cost than generating profit. The findings on determinants of bank efficiency using bank specific, macroeconomic specific and industry specific determinants vary between countries but do significantly contributes towards bank efficiency. There was evidence of causality relationship between bank efficiency and economic growth which implies no long run relationship between these variables where in both case the null hypothesis of no cointegration cannot be rejected. Nonetheless, in almost all cases there is a Granger causality relationship between bank cost efficiency and economic growth and between bank cost efficiency and profit efficiency, suggesting that more cost efficient bank are also the more profit efficient bank. For the bank management behavior perspective, the findings suggests that the ‘bad luck’ hypothesis applies to commercial banks in Algeria and Nigeria but not for banks from Egypt, Kenya, South Africa and Tanzania.When banks were classified on group of countries basis, unlike the commercial banks in Kenya and Tanzania, the bad luck hypothesis supports the behavior of commercial banks in the SENA region. The bad management hypothesis explains the behavior of commercial banks in the SENA region but not for banks in the Kenya and Tanzanian region.